Microbiome in maintained periodontitis and its shift over a single maintenance interval of 3 months. (28th August 2019) - Lu, Hongye; Zhao, Yibing; Feng, Xianghui; He, Lu; Meng, Huanxin
Abstract: Aim: To assess the subgingival microbial shift of maintained periodontitis treated by ultrasonic scaling (US) or air polishing (AP) during a 3‐month maintenance interval. Materials and methods: We conducted a 12‐week randomized split‐mouth controlled trial with US and AP in 17 maintained subjects (bleeding on probing [BOP%] ≤25%, probing depth [PD] ≤5 mm). They were monitored at baseline, week 2, week 8 and week 12. The V3‐V4 region of the 16S rDNA from 136 subgingival plaque samples was sequenced and analysed. Results: Treatment by US or AP could effectively reduce the PD, microbial richness, diversity, periodontitis‐associated microbiota and pathogenic metabolism in maintained periodontitis. Bacteria recolonized after treatment and returned to the pre‐treatment level 12 weeks after treatment. Ultrasonic scaling group demonstrated slight advantage in reducing BOP (%), pathogenic bacteria and metabolism than AP group. Pathogenic microbiota and commensal microbiota kept a balance in subgingival community of maintained patients during the 3‐month interval. Conclusions: Treatment by US or AP effectively reduced the pathogenicity of subgingival microbiome by reducing microbial diversity, proportion of periodontitis‐associated microbiota and pathogenic metabolism. It helped to keep a balanced subgingival community and stable periodontal condition over a single maintenance interval of 3 months.